Consórcio de culturas de interesse zootécnico para produção de silagem - Pedro Guilherme Ramme de Freitas (2023)
Intercropping between forage can improve the characteristics and nutritional value of silage. The objective was to evaluate the production of green matter, bromatological composition, pH, gas loss and in vitro dry matter dispearance and neutral detergent fiber of intercropped silages. A randomized block design with five treatments (corn + millet, corn + pigeonpea, millet + pigeonpea, single corn and single millet) and four replications was used. Yield per hectare, bromatological chemical composition, fermentation parameters such as pH and gas loss and in vitro dry matter dispearance and neutral detergent fiber were evaluated. The highest productions of green matter verified were in millet + pigeon pea (38.55 tons per hectare) and millet (35.72 tons per hectare). Higher dry matter contents (45.16%) and (42.92%) were observed in corn and corn + pigeon pea silages, respectively. Higher organic matter (95.81%; 95.56% and 94.60%) were observed in silages that have corn in their composition. Higher amounts of mineral material (5.74%; 5.50% and 4.98%) occurred in silages that have millet in their composition. Values found for neutral detergent fiber (70.66%; 70.06 and 67.43) and acid detergent fiber (48.65%; 48.65% and 45.76%) were higher in silages that used millet. Crude protein values were higher in millet silages intercropped with pigeon pea (11.67%). The highest values for ether extract verified were corn + pigeon pea (3.14%); millet + pigeon pea (3.12%); corn (2.68%) and corn + millet (2.43%). The highest nonstructural carbohydrates content was observed in corn silage (30.74%). The highest pH values (3.89) and (3.78) were observed in corn + pigeon pea and single corn silages, respectively. There was no difference for gas losses (P-value = 0.318). The highest values of in vitro dry matter dispearance were observed in corn silages (68.36%). For in vitro neutral detergent fiber dispearance there were no differences (P-value = 0.2093). It is concluded that due to the greater production of green matter, nutritional value and fermentative parameters presented, the material that best stood out was millet silage intercropped with pigeon pea. Keywords: Cajanus cajan, forage intercropping, Pennisetum glaucum, silage, Zea mays.